2006
DOI: 10.1299/jsmeb.49.1165
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Characteristics of Under-Expanded Condensing Jet

Abstract: The single supersonic free jet discharging from a nozzle or an orifice has been often employed in various industrial processes. A number of studies have been done on the major features (Mach disk, barrel shock wave and the jet boundary configuration) of the supersonic jets. In the present study, numerical computations were performed to investigate the effect of initial degree of supersaturation of moist air at reservoir condition on under-expanded jet structures and the total pressure loss behind the Mach disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This is certainly the most studied feature in the literature, be it experimentally [12,30,35,40,43,49,51,[56][57][58][59]62,64,, theoretically [13,29,67,76,78,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] or numerically [14,20,22,34,41,59,63,75,81,82,84,91,[110][111][112][113][114][115][...…”
Section: The Mach Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…This is certainly the most studied feature in the literature, be it experimentally [12,30,35,40,43,49,51,[56][57][58][59]62,64,, theoretically [13,29,67,76,78,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] or numerically [14,20,22,34,41,59,63,75,81,82,84,91,[110][111][112][113][114][115][...…”
Section: The Mach Diskmentioning
confidence: 99%
“…16] or [11,Chap. 7] but the moment when this phenomenon occurs is quantitatively poorly known, especially the dependency (and interactions) on the pressure [96,29,62,30,[98][99][100]12,64,123,43,124,84,13,107,90,54]. Nonetheless, among the theoretical studies, the Mach disk location has been supposed to appear at a position such that the conservation equations are satisfied for the section perpendicular to the axis [95].…”
Section: The Mach Diskmentioning
confidence: 99%
“…N2 has a convergence angle b ¼ 751 at the entrance, while N3 has b ¼ 901, but the orifice exit diverges with 451 over the length 0.5D e . (Otobe et al, 2006). The shadowgraph visualization is shown in the lower half, while the present computational results are given as predicted isodensity contours in the upper half.…”
Section: Nozzle Geometriesmentioning
confidence: 99%
“…As in most of the engineering applications of supersonics jets, the working gas is usually steam or moist air and the moist air jets are qualitatively similar to dry air, but non-equilibrium condensation in moist air jet affects the shock configuration, reported by Baek et al [9] and Otobe et al [10]. Meanwhile, Kim et al [11] and Otobe et al [12] have investigated the effect of non-equilibrium condensation on the hysteresis phenomenon of under-expanded supersonic jets and reported that the moist air jet reduced the hysteretic phenomenon compared with the dry air jet, and the non-equilibrium condensation that occurs in the under-expanded moist air jet is responsible for these findings.…”
Section: Introductionmentioning
confidence: 99%